O tratamento de dados pessoais em perspectiva comparada entre União Europeia e Brasil: o papel da autoridade nacional de proteção de dados como instrumento para a tutela de direitos fundamentais - Lima, Wiliam Costodio (2020)
The network society is marked by the intense use of information and communication technologies (ICT). This informational flow generates a significant amount of personal data and its treatment has been the subject of normative attention in technologically developed countries, not in Brazil, since the 1970s, in view of the potential risks of this dynamic. In view of this, this study aims to critically analyze the risks to fundamental rights derived from the use of personal data by States and the market to verify and discuss the legal treatment of the topic in a comparative perspective between the European Union and Brazil, examining how these laws deal with regulation of informational flows and instruments designed for data protection, with emphasis on the work of the National Data Protection Authority. Such investigation is in harmony with the line of research Rights in the network society: actors, factors and processes in the globalization, of the Postgraduate Program in Law and, starting from this scenario of informational flows, the aim is to answer the following research problem formulated: will the recent regulatory framework issued in Brazil regarding the protection of personal data and the creation of the National Data Protection Authority (ANPD) allow the country to be considered with the same normative level of protection as the European Union? The theoretical framework of this work is composed by Antonio Enrique Pérez Luño and Danilo Doneda, and the deductive approach method is used, with the comparative procedure and techniques of document analysis and bibliographic research. The results showed that the performance of the National Data Protection Supervisor in Brazil will be decisive for the country to be considered at an acceptable level for the protection of personal data and thus contribute to the control of the risks arising from its processing and use by States and by the market. The findings suggest that Brazil may reach a level compatible with the European data protection system considered one of the most advanced for multisector internet governance initiatives, although the risks of data processing still exist due to the characteristics Internet and its ambivalence. It is recommended to include data protection in your list of fundamental rights, as well as the guarantee of a protection authority to monitor compliance with the rules related to the matter.